Newborn Calf Circumference to Identify Low Birth Weight Neonates - Atriadewi, Hambrah Sri; Hafidh, Yulidar; Andarini, Ismiranti (Journal of Maternal and Child Health, 2024)
Background: The absence of birth weight records for infants remains a prevalent issue in developing countries, including Indonesia. The timely identification of low birth weight (LBW) and premature neonates, particularly those born outside well-equipped healthcare facilities is vital within the critical first 48 hours of life. This study aimed to ssess the potential utility of calf circumference in identifying low birth weight infants. Subjects and Method: A cross-sectional study was conducted on 100 neonates aged between 0 – 48 hours old who were treated at Dr. Moewardi General Hospital, Surakarta from May 2022 to August 2022. The dependent variable was neonates birth weight. The independent variables was calf circumference. Calf circumference was measured using non elastic but flexible measuring tape, with measurement precision up to the nearest 0.1 cm. The cut-off point of calf circumference was determined with the ROC curve. Results: Calf circumference significantly correlates with birth weight (p<0.001), with r=0.969. The calf circumference cut-off value of 10.35 cm in LBW had an AUC of 0.99, a sensitivity of 98.0%, a specificity of 98.0%, and a positive predictive value of 98.0%, a negative predictive value of 98.0%. The calf circumference cut-off value was 8.85 cm for LBW neonates, which had an AUC of 0.93, with a sensitivity of 83.9%. specificity 85.7%, positive predictive value 98.7%, negative predictive value 28.6%. Conclusion: Calf circumference in newborns can be used to identify neonates with low birth weight.